2001
DOI: 10.1149/1.1353579
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen on Thermocapillary Convection in a Molten Silicon Column under Microgravity

Abstract: X-ray flow visualization in a half-zone molten silicon bridge was carried out under microgravity at a variety of oxygen partial pressures in an ambient atmosphere. The flow velocity of thermocapillary convection was found to decrease with increased oxygen partial pressure. Thermocapillary flow stabilized when the oxygen partial pressure at the inlet p O 2 was increased to 10 Ϫ4 MPa. The dependence of the flow velocity and flow mode on p O 2 can be explained in terms of the decrease in the temperature coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…4.17(a) and (b). The oxygen partial pressure dependence of the Marangoni flow velocity for molten silicon observed under microgravity conditions [81] was well explained by taking account of the oxygen partial pressure dependence of the temperature coefficient of surface tension.…”
Section: Surface Tensionmentioning
confidence: 85%
“…4.17(a) and (b). The oxygen partial pressure dependence of the Marangoni flow velocity for molten silicon observed under microgravity conditions [81] was well explained by taking account of the oxygen partial pressure dependence of the temperature coefficient of surface tension.…”
Section: Surface Tensionmentioning
confidence: 85%
“…The Marangoni flow shows a marked dependence on oxygen partial pressure of an ambient atmosphere, i.e. oxygen concentration in the melt [37]. This flow shows a unique behavior at the surface of the Czochralski melt, because the oxygen concentration is high in the melt adjacent to the crucible wall and low in the vicinity of the growing crystal.…”
Section: Analysis Of Heat-and Mass-transfer Processesmentioning
confidence: 96%
“…This idea has been based on the measurement of surface tension of molten silicon as a function of temperature and oxygen partial pressure; both surface tension and temperature coefficient show marked dependence on the ambient oxygen partial pressure [22]. We found that both flow velocity and instability mode of the Marangoni flow are consequently affected by oxygen partial pressure [12,13]. We have tried to find the effect of oxygen partial pressure on striation formation of the silicon crystals, because striation is introduced by instability of the Marangoni flow.…”
Section: Introductionmentioning
confidence: 92%
“…Prof. Benz's group and our group shared these challenging subjects and collaborated. Research activities of the Japanese group featured diagnostics of the Marangoni flow from the viewpoint of hydromechanics, i.e., temperature fluctuation measurements using multiple thermocouples [10], in-situ visualization of the Marangoni flow using an X-ray technique [11] and observation of the effect of oxygen partial pressure on the Marangoni flow [12,13]. The existence of the critical Marangoni number Ma c3 , where an oscillatory flow with a single frequency changes into that with multiple frequencies, was observed for the first time [11,13].…”
Section: Introductionmentioning
confidence: 99%